Interpretasi Film Budi Pekerti: Antara Moral Dan Viral - Ari Amalia Rossiana; Rijalul Haq; Indriyati Konga Naha; Eni Nurhayati (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of the world of cinema is currently growing rapidly, including in Indonesia. Various film themes have been produced as a means of entertainment and conveying messages to audiences. This research aims to describe the message conveyed in a film by analyzing the content qualitatively in the presentation of the story of the film